Impact of the pandemic on leisure physical activity and alcohol consumption - Fredrik Granström; Marika Wenemark; Karin Festin; Elin Good; Helena Frielingsdorf; Mats Lowén; Ingrid Rystedt (BMC, 2024)
Abstract Background The COVID-19 pandemic precipitated heightened morbidity and elevated mortality attributed to the SARS-CoV-2 infection. The pandemic also influenced health behaviors such as physical activity (PA) and alcohol consumption. The aim of this study was to examine changes in leisure PA and alcohol consumption in Sweden during the pandemic, and elucidate potential discrepancies in changes across demographic strata and socioeconomic status (SES). Methods Data were retrieved from two waves of the longitudinal cohort study Life conditions, Stress and Health (LSH) (n = 2,523). Two measures of change were used; longitudinal change relative to baseline (2012-2015) and reported change compared to before the pandemic. For these two change measures, differences between sex, age group and SES were analyzed using multinomial logistic regression. Results Regardless of the change measure, the proportion of individuals with diminished PA was notably higher among females compared to males. Furthermore, relative to baseline, females were less likely to have increased their PA, however according to the reported change they were more likely to have increased PA. Longitudinal change in PA compared to baseline followed a reversed age gradient, while, according to reported change, a decrease in PA during the pandemic was most prevalent in respondents 45 years of age at baseline (OR = 1.8, CI: 1.2-2.5) and respondents 50 years of age at baseline (OR = 1.7, CI: 1.2-2.4). High SES was associated with a greater variability in PA. Alcohol consumption was generally reduced during the pandemic. However, individuals aged 40 or 45 years at baseline were more likely than others to have initiated risky alcohol consumption. Conclusions Females exhibited a greater propensity to alter their PA levels during the pandemic, with the most profound decreases observed among individuals of working ages. Despite a general downturn in alcohol consumption, individuals aged 40 and 45 had a heightened likelihood of having initiated risky alcohol consumption compared to individuals in other age cohorts. In conclusion, societal restrictions during a pandemic render a dual impact on PA levels. While posing a risk for decreased PA among individuals in working ages, the restrictions also present a potential window of opportunity to increase PA, particularly among females.